Term system as a dynamic structure (Eurasian Journal of Philology Science and Education, 2016)
Term building remains one of the major problems of the modern linguistics in spite of diverse investigating the issue. The experiences show that the terminological activity in each area depends on the productivity of the industry where the new concepts are created. Term system is a dynamic structure, capable of improvement and development, at every stage of its formation represents the locked set of linguistic concepts. The term system, established by Lev Gumilyov has a wide range of nominative means to transmit the nuances of similar value concepts. The terms in the writings of Lev Gumilyov serve not only to refer to the new objects and phenomena, but also participate in the increment of knowledge. According to Lev Gumilyov’s opinion, the formation of new terms is subject to certain laws. Of all the possible options of term building he selects those that are able to most accurately capture the essence of the object or phenomenon that must nominate. Thus, the analysis of the meaning of a particular term is only possible on the basis of cognitive analysis, including the study of the system of values and lexical units.
Keywords: Term system; mechanisms of term building; terms; dynamic structure.